Susceptibility of strict and facultative anaerobes Isolated from endodontic infections to metronidazole and beta-lactams - Elerson Gaetti-Jardim Júnior; Luís Fernando Landucci; Samira Âmbar Lins; Evanice Menezes Marçal Vieira; Sérgio Ricardo de Oliveira (University of São Paulo, 2007)
Endodontic infections are mixed aerobic-anaerobic infections and several microbial groups associated to these pathologies are also involved in orofacial infections. The goal of this study was to evaluate the susceptibility of microorganisms isolated from endodontic infections to beta-lactams and metronidazole and verify the production of beta-lactamases. Clinical specimens were collected from 58 endodontic infections of 52 patients. The microorganisms were isolated in selective and non-selective culture media, under anaerobiosis and aerobiosis, and identified using biochemical methods. In the susceptibility tests, it was used an agar dilution method, and Wilkins-Chalgren agar enriched with blood, hemin and menadione for the anaerobes, while Mueller-Hinton agar was employed for the facultative anaerobes. The production of beta-lactamases was evaluated through the biological and chromogenic cephalosporin methods. All tested isolates were sensitive to imipenem and 99.3% to amoxicillin/clavulanate association, while 16.1% showed resistance to amoxicillin and penicillin G, and 4.89% to cefoxitin. Resistance to metronidazole was just found in facultative anaerobes. Production of beta-lactamases was detected in 18.2% of the isolates and presented a correlation with resistance to beta-lactams.